Satire Journalism: Semiotic Analysis of Pilpres 2024 Articles on Mojok.co" - Rosdiana Rosdiana; Wahyunengsih Wahyunengsih (Jurnal Komunikasi, 2023)
This study aims to analyze the practice of satire journalism in Mojok.co through Charles S. Peirce's semiotic approach. The research method used is descriptive qualitative research. This research focuses on analyzing articles about the 2024 presidential election published in the essay section of Mojok.co. In this study, researchers explored how satire in this context uses signs and symbolic interpretations based on the semiotic theory applied. In addition, the researcher is also interested in knowing how the use of satire language style can affect readers' perceptions and understanding of the political issues presented. The results of this study conclude that Mojok.co sometimes violates the journalistic code of ethics in presenting satire content. This can reduce the integrity of journalism and lead to misunderstanding of the subject being criticized. However, this study also found that Mojok.co has the power to attract readers and raise political issues through its satire style. This research provides insight into how media can shape audience understanding and interpretation through the use of signs, objects and interpretants in the practice of satire journalism.